The relationship of eating until 80% full with types and energy values of food consumed. (April 2015) - Fukkoshi, Yuko; Akamatsu, Rie; Shimpo, Misa
Abstract: Objective: Eating until one is 80% full is considered a healthy dietary practice in Japan. This study examined the relationship between this behavior and energy intake and types and quantities of foods consumed to examine its beneficial effects. Methods: This study relied on dietary records and self-administered questionnaires completed by 330 users of a health-management website in November 2012. ANOVA was performed to examine the relationship between eating until one is 80% full and intake. Results: Men who always ate until they were 80% full consumed less energy than those who did not (mean [ SD ]; always: 1997.3 [356.7] kcal; rarely/never: 2448.9 [637.1] kcal; p < 0.05). Moreover, men who ate until they were 80% full consumed fewer servings of grain dishes (always: 3.7 [0.9] servings; rarely/never: 5.1 [1.9] servings; p < 0.05) and more servings of vegetable dishes (always: 5.9 [2.2] servings; rarely/never: 4.0 [2.3] servings, p < 0.05) than those who did not. Conclusion: Men who ate until they were 80% full consumed less energy and more vegetable dishes than those who did not, suggesting that eating until one is 80% full is associated with healthy dietary habits among men. Highlights: Men who always ate until they were 80% full consumed less energy than those who did not. Men who always ate until they were 80% full consumed fewer servings of grain dishes and more servings of vegetables. Among women, there was no difference for the types or energy values of food consumed except regarding BMI.